Potential of Bintangur (Calophyllum spp.) Diversity in West Kalimantan as a Biology Learning Resource in Senior High School - Faturrahman, Mas Akhbar; Ningsih, Kurnia; Sandra, Klaudia Mareta; Astuti, Widya; Isyatirradhiyah, Isyatirradhiyah; Ayu, Nambisas Arum Kusuma; Salsabila, Nur; Afifah, Artha Bayu; Perdana, Aurendyo Yuscel (Jurnal Pijar Mipa, 2024)
Indonesia is one of the countries with a very high level of biodiversity. West Kalimantan is one of the provinces with the highest level of biodiversity in Indonesia. One form of biodiversity found in West Kalimantan's forests is bintangur (Calophyllum spp.). The very high diversity of bintangur species is fascinating to be utilized as a source of learning biology, especially in the material of biodiversity and their interactions and roles. This study aimed to analyze the potential of bintangur diversity in West Kalimantan as a biology learning resource on the material of biodiversity and their interactions and roles in senior high school. This research uses the qualitative method. This research consists of two stages. The first stage is a literature review to find information related to bintangur species in West Kalimantan. In contrast, the second stage is an analysis of learning resource requirements based on the results of the literature review that has been carried out. The results of the literature review stage show that there are 27 species of bintangur in West Kalimantan, as well as their classification, main characteristics, habitats, and values to the environment and other organisms. The literature review stage results are then continued to the learning resources analysis. Six requirements must be met for learning resources: clarity of the potential availability of objects and problems raised, suitability for learning objectives, clarity of targets and their designation, clarity of information disclosed, clarity of exploration guidelines, and clarity of the results to be achieved. The analysis of learning resource requirements that have been carried out shows that the diversity of bintangur species in West Kalimantan meets the requirements of learning resources so that it can be utilized as a biology learning resource on the material of biodiversity and their interactions and roles in senior high school.